The role of vitamin D in alopecia areata - Chyl-Surdacka, Katarzyna; Gerkowicz, Agnieszka; Chodorowska, Grażyna (Dermatology Review/Przegląd Dermatologiczny, 2016)
Alopecia areata is an inflammatory disease with noncicatricial hair loss. Despite its high prevalence in the dermatological patient population, the pathogenesis is not sufficiently understood. In recent years, the contribution of autoimmune processes has been emphasized, as indicated by the presence of autoantibodies against hair follicle antigens and inflammatory cell infiltrates with increased expression of cytokines around the hair follicle. Vitamin D performs many important functions in the human body – is responsible for maintaining calcium homeostasis but is also an important regulator of the immune response. It acts mainly via the nuclear vitamin D receptor located on the surface of dendritic cells, macrophages, B and T cells, keratinocytes and cells of the hair follicle papillae. Vitamin D suppresses the immune system cells, and its deficiency may be important in pathophysiological phenomena in alopecia areata. According to current data, vitamin D supplementation may be a therapeutic option worth considering in patients with alopecia areata.